1979
DOI: 10.1136/vr.104.13.281
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation rate and egg recovery in cattle treated repeatedly with pregnant mare serum gonadotrophin and prostaglandin

Abstract: Fourteen heifers were superovulated five to 10 times using pregnant mare serum gonadotrophin (PMSG) and prostaglandin in a standardised regime which resulted in a mean interval of 42.1 days (SEM +/- 0.97) between treatments. There was a significant (P less than 0.02) fall in the mean ovulation rate at the second treatment when compared with the first but no significant difference between mean ovulation rate at the second and subsequent treatments. No significant difference between treatments in mean egg recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In cattle, eCG is largely used in zootechnical programs in order to stimulate follicular growth and ovulation: treatment of anoestrus [19], synchronisation or induction of oestrus in combination with progestagens (400 to 600 IU once a year) [7,12], induction of superovulation (1 000 to 2 000 IU) [2,16,35] and more recently, stimulation of follicular growth in ovum pick-up programs (OPU) [15,21]. The higher doses and the higher frequency administration of eCG in OPU programs may have an influence on eCG antibody production in the cow and may induce a reduction in the efficiency of such treatments.…”
Section: Radiolabeling With 125 Iodinementioning
confidence: 99%
“…In cattle, eCG is largely used in zootechnical programs in order to stimulate follicular growth and ovulation: treatment of anoestrus [19], synchronisation or induction of oestrus in combination with progestagens (400 to 600 IU once a year) [7,12], induction of superovulation (1 000 to 2 000 IU) [2,16,35] and more recently, stimulation of follicular growth in ovum pick-up programs (OPU) [15,21]. The higher doses and the higher frequency administration of eCG in OPU programs may have an influence on eCG antibody production in the cow and may induce a reduction in the efficiency of such treatments.…”
Section: Radiolabeling With 125 Iodinementioning
confidence: 99%
“…Although some studies showed no significant reduction of ovulation in repeated treatments [34][35][36], other studies indicated r e d u c e d r e s p o n s e s t o s e c o n d a n d l a t e r superovulatory treatments of cows in consecutive years [9,37,38] and within the same year [8,[39][40][41]. About 15 to 20 eggs in total were usually collected from the first three flushings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on cattle (Willet et al, 1953;Christie et al, 1979;Alwan et al, 1988), and goats (Maurer et al, 1968;Gherardi and Martin, 1978;Armstrong et al, 1983;Remy et al, 1991;Baril et al, 1992b;Beckers et al, 1995) (Pignon et al, 1960;Jainudeen et al, 1966;Maurer et al, 1968;Alwan et al, 1988;Bavister et al, 1986;Remy et al, 1991;Baril et al, 1992b). Moreover, Beckers et al (1995) showed that goats treated with eCG, transmitted anti-eCG antibodies in their colostrum.…”
mentioning
confidence: 99%
“…Several studies in cattle sheep and goats have shown that for large scale superovulation, porcine pituitary extract (Willet et al, 1953;Remy et al, 1991;Staigmiller et al, 1992) or a crude extract of PMSG (Willet et al, 1953;Gherardi and Martin, 1978;Christie et al, 1979;Armstrong et al, 1983;Bavister et al, 1986;Baril et al, 1992a, b;Beckers et al, 1995) can be used as a source of FSH activity. However, for oestrus synchronisation even though pFSH can be used, PMSG is preferable because it is administred in a single dose.…”
mentioning
confidence: 99%